A verisimilitude of pessimism: Scottish prisoner mug-shots, 1883–1927. Issue 2 (3rd April 2018) - HOLLIGAN, Chris; MAITRA, Dev
Abstract : This paper examines the stigmatisation of identity. Historic prisoner mug shots taken in two Scottish prisons during the late Victorian period constitute a part of archival base of this study from which generalisations to the contemporary world are conjectured. Cultural criminologists propose crime is normatively framed. Mug shots belong with a larger symbolism within a discourse of crime and culture. This article examines the scientific and cultural environs within which a dangerous semiotic of the mug shot image originated. The 'gaze' of the mug shot, it is argued, suffers from class stigmata circulating elite Victorian scientific laboratories and drawing-rooms. Criminal anthropology, it is argued, constructed visual sources as tools for reaching certainty, but in this project generated processes of social closure. Morphological deviations from the norm defined the 'criminal body'.